Water Adsorption Dynamics on Metal–Organic Framework MOF-801: Comparative Study of Loose and Glued Grains, and Coatings - Solovyeva, Marina; Gordeeva, Larisa (Nanomaterials (Basel, Switzerland), 2023)
Adsorption heat transformation and storage (AHTS) is an environmentally benign and energy-saving alternative to common compression chillers and heat pumps. The low specific power (SP) of adsorption systems is a key drawback that hinders their broader dissemination. The optimization of adsorption dynamics is a prerequisite for SP enhancement. In this work, we studied the dynamics of water vapor adsorption on MOF-801—a promising adsorbent for AHTS. For the first time, two configurations of compact MOF-801 bed, namely, grains glued to the surface of a metal support and thin adsorbent coatings, are prepared, and their porous structure is characterized. The water adsorption dynamics is compared with a common loose grains configuration. The main findings are: (a) the binder can both accelerate and decelerate the water adsorption, and its chemical nature is subject to careful selection; (b) at the initial time, heat transfer between the support and adsorbent bed controls the adsorption rate, and, at a longer time, mass transfer starts to affect it; (c) polyvinylpyrrolidone, bentonite, thermal grease, and hydroxyethylcellulose increase the heat transfer coefficients and accelerate adsorption; polyvinyl alcohol and polyaniline slow it down; and (d) for the coatings prepared with polyvinylpyrrolidone, an SP of 1.6–5.1 kW/kg can be achieved, which is about twice that for the loose grains. The new configurations can be recommended for effective but expensive adsorbents such as MOFs, and their implementation will contribute to the further spread of AHTS technology.